Detection of interictal epileptiform discharges in an extended scalp EEG array and high-density EEG-A prospective multicenter study - Heers, Marcel; Böttcher, Sebastian; Kalina, Adam; Katletz, Stefan; Altenmüller, Dirk-Matthias; Baroumand, Amir G; Strobbe, Gregor; van Mierlo, Pieter; von Oertzen, Tim J; Marusic, Petr; Schulze-Bonhage, Andreas; Beniczky, Sándor; et al. (Epilepsia, 2022)
OBJECTIVES: High counts of averaged interictal epileptiform discharges (IEDs) are key components of accurate interictal electric source imaging (ESI) in patients with focal epilepsy. Automated detections may be time-efficient, but they need to identify the correct IED types. Thus we compared semiautomated and automated detection of IED types in long-term video-EEG (electroencephalography) monitoring (LTM) using an extended scalp EEG array and short-term high-density EEG (hdEEG) with visual detection of IED types and the seizure-onset zone (SOZ). METHODS: We prospectively recruited consecutive patients from four epilepsy centers who underwent both LTM with 40-electrode scalp EEG and short-term hdEEG with 256 electrodes. Only patients with a single circumscribed SOZ in LTM were included. In LTM and hdEEG, IED types were identified visually, semiautomatically and automatically. Concordances of semiautomated and automated detections in LTM and hdEEG, as well as visual detections in hdEEG, were compared against visually detected IED types and the SOZ in LTM. RESULTS: Fifty-two of 62 patients with LTM and hdEEG were included. The most frequent IED types per patient, detected semiautomatically and automatically in LTM and visually in hdEEG, were significantly concordant with the most frequently visually identified IED type in LTM and the SOZ. Semiautomated and automated detections of IED types in hdEEG were significantly concordant with visually identified IED types in LTM, only when IED types with more than 50 detected single IEDs were selected. The threshold of 50 detected IED in hdEEG was reached in half of the patients. For all IED types per patient, agreement between visual and semiautomated detections in LTM was high. SIGNIFICANCE: Semiautomated and automated detections of IED types in LTM show significant agreement with visually detected IED types and the SOZ. In short-term hdEEG, semiautomated detections of IED types are concordant with visually detected IED types and the SOZ in LTM if high IED counts were detected.
Keywords: Scalp; magnetická rezonanční tomografie; elektroencefalografie; lidé; Prospective Studies; Epilepsies, Partial; záchvaty; Electroencephalography; Magnetic Resonance Imaging; Humans; Seizures; epilepsie parciální; prospektivní studie; skalp